Long term survival among patients who are disease free at 1-year post allogeneic hematopoietic cell transplantation: a single center analysis of 389 consecutive patients. (May 2018) - Solh, Melhem; Bashey, Asad; Solomon, Scott; Morris, Lawrence; Zhang, Xu; Brown, Stacey; Holland, H. Kent
Abstract Allogeneic hematopoietic cell transplantation (HCT) is associated with significant morbidity and mortality especially in the first year after HCT. In this study, we examine the long-term outcomes of patients who survived at least one year post HCT without evidence of relapse. We analyzed the records for 389 consecutive patients receiving an allogeneic transplant from 2005 to 2016 from a MRD, MUD, or haploidentical donor, who were alive and disease free at one year post-transplant. Patient characteristics and outcome parameters were extracted from our institutional database where they had been prospectively entered. A total of 389 patients met the selection criteria with donor graft including MRD 37%, MUD 39%, and Haploidenitcal relative 24%. The median follow-up of survivors from time of HCT was 48.2 months. The median overall survival and disease-free survival at 5 years after the first anniversary post HCT was 78 and 74%, respectively. The most common causes of late mortality were disease relapse, chronic GVHD and infections. The major risk factors for late mortality included chronic GVHD requiring immunosuppression, being transplanted between 2005 and 2009 compared to later years and male sex. Patients with high risk disease risk index (DRI) had worse OS compared to low risk DRI. The risk factors for late relapse included male sex and high/very high disease risk index. The projected long-term survival of 1-year survivors following allogeneic HCT is excellent. However, some patients remain at high risk of late relapse and late mortality. Early referral to transplant, adopting post-transplant consolidation strategies for high risk patients, and implementing newer GVHD prevention methods are potential interventions to help minimize the risk of late relapse and death.